RHETORICAL MOVES DALAM INDUKSI HIPNOTERAPI: ANALISIS GENRE - Nurul Ashyfa Khotima; Dadang Sudana; Wawan Gunawan; Jatmika Nurhadi; Sintia Hapsyah Rahman (Jurnal Semantik, 2023)
Hypnotherapy can be used as an effective therapy to overcome certain symptoms and conditions by entering the subconscious mind and giving positive suggestions to clients. When a therapist provides hypnosis, there is a distinctive linguistic structure. This structure can be analyzed using genre analysis. This study will focus on genre analysis in hypnotherapy induction by looking at the rhetorical moves structure of each hypnotherapy technique performed. In this research, the descriptive qualitative method is used, which aims to describe the rhetorical moves contained in the hypnotherapy induction script. The data used in this study were obtained from the Indonesian Board of Hypnotherapy training module in as many as five induction scripts. The technique used to analyze the data was immediate constituent analysis of each utterance in the hypnotherapy induction script. This research produces 20 rhetorical moves that have been classified from 203 utterances contained in the hypnotherapy induction script. Based on the speech acts, rhetorical moves in hypnotherapy are characterized by performative verbs commanding, declaring, informing, and praising, such as the use of the verbs pay attention, relax, imagine, and feel. The results show similarities and differences in the structure of rhetorical moves that can change and are not fixed.